Mathematical Literacy and Curiosity Through Creative Problem Solving Learning Using the PMRI Approach Assisted by Photomath - Pamungkas, Reki Gilang; Wardono, Wardono; Agoestanto, Arief (Didactical Mathematics, 2024)
This study aims to show (1) the quality of Creative Problem Solving learning with PMRI approach assisted by Photomath to improve students' mathematical literacy; (2) test the effect of curiosity on students' mathematical literacy through Creative Problem Solving learning with PMRI approach assisted by Photomath. This research is a type of quantitative research using Quasi Experimental on Pretest-Posttest Control Group Design. The population in this study were VIII grade students of SMPN 02 Kaliwedi, Cirebon Regency. Data analysis on learning quality includes the preparation stage, implementation stage and learning evaluation stage. Quantitative data analysis at the learning evaluation stage includes prerequisite tests consisting of normality test, homogeneity test, mean similarity test, while hypothesis testing consists of one sample average test referring to BTA; classical completeness proportion test; 2 mean difference test; 2 proportion difference test; test for average increase in mathematical literacy; and simple linear regression test. The results proved that (a) learning with CPS model with PMRI approach assisted by Photomath was qualified in improving mathematical literacy; (b) curiosity influenced 73.2% of students' mathematical literacy.